"Come on Down": Using a Trivia Game to Teach the Concept of Organizational Justice. (September 2021) - Swain, Jordon E.; Bogardus, Jason A.; Lin, Eric
The three elements of organizational justice (distributive, procedural, and interactional justice) can be difficult for undergraduate students to grasp given variances in their personal experiences. To address this issue, we developed a novel approach to teach students these concepts by employing a trivia game show format in which students experience all three forms of injustice in a lighthearted and disarming context. We detail this experiential exercise and provide discussion points to help students grasp the important role organizational justice plays in leading effectively. We also provide suggestions for how to apply the concepts covered in the experiential exercise to different leadership challenges to deepen the learning experience.